Compaction parameters of reinforced clayey sand - Chegenizadeh, Amin; Nikraz, Hamid (WASET, 2011)
Composite soils have been widely used in civil engineering applications, especially in slopes, embankment dam and landfills. This paper aims to investigate effect of fibre inclusion on compaction characteristic of composite soil (i.e. clayey sand composite). A series of laboratory tests carried out to evaluate fibre effect on optimum water content and maximum dry unit weight of composite soils. Clayey sand was selected as soil part of the composite and natural fibre was used as reinforcement. The fibre parameters differed from one test to another, as fibre length varied from 15 mm to 30 mm and fibre content were selected as 0.5% and 0.7%. For each test, compaction curved derived and the results were compared. The results proved that inclusion of fibre affected compaction behaviour of samples so that increasing in fibre content and length caused increasing in Optimum Moisture Content (OMC) and slightly decreased maximum dry unit weight.